O imaginário e a formação docente: reflexões sobre a docência universitária a partir de uma cultura colaborativa - Vasconcellos, Vanessa Alves da Silveira de (2017)
The investigative efforts of this research center on the theme of the teacher of higher education and for the formation of the professional that works at this level of education from the theory of the imaginary. This thesis that is part of the Post-Graduate Program in Education at the doctoral level in the Line of Research Training, Knowledge and Professional Development of the Federal University of Santa Maria, focuses on a proposal of work through collaborative practices to think the training, presenting the following problem: In what way does a proposal of work through collaborative practices favor the formation of the teacher of higher education? If you want to defend here the forms of interactions between faculty peers, which go beyond the brief and superficial conversations of corridors and departments, for a consistent exchange between looks and conceptions, from observations and reflections in and about practice, resulting in new meanings in university teaching. The research has the following objectives: General: To understand the impact and the way in which the collaborative practices favor the formation of the teacher of higher education and (res) mean the pedagogical practices of the university professor; specific: To understand the processes and training dynamics developed by teachers who participate in a collaborative experience; investigate the potential of empathic observation as a practice of reflection and sharing by higher education teachers; know the different types of teacher and university teaching in different areas of knowledge and professional cultures. With the intention of bringing to the debate the discussions of the formation of university professors, based on a collaborative practice, the studies based on the social Imaginary make possible, in addition to the construction of a theoretical conception, an understanding of differentiated epistemological and methodological conceptions. thus presenting as a methodological contribution of this project the biographical approach, having as input the data in the narratives, the focus group and the empathic observation. Thus, the thesis here advocated believes in the formative power of the action of empathic observation, as a possibility of a displacement of meaning, where the available symbols are invested with other meanings, new and reworked, in a res-signification of the formative practices in teaching university It was possible to detect in the production of this thesis that the development of practices that promote the sharing, the collaboration, the support in the colleague. This affirmation was evidenced by the fact that it is from the trust between peers that teacher learning is favored by powerful encounters, from which the ways of thinking, acting and comprehending reality are expanded, as well as enabling (trans) formation in the exercise of teaching.